Online sports fans communities: humor, trivial knowledge, and anti-modern tendencies - Levental, Orr (Frontiers in Sports and Active Living, 2023)
Recent technical developments and the widespread use of social networks have led to the emergence of a variety of online communities built around common interests. Among these virtual communities, one notable category revolves around sports fans. This conceptual article uses several examples of online sports fan communities in Israel to analyze their core elements. Within this context, the article focuses on the significance of humor, trivial knowledge, and counter-modern concepts as the key elements fostering unity among fans. Humor serves as a common thread that encourages interactions, also providing a platform for fans to showcase their niche knowledge, symbolizing their dedication to fan culture. Meanwhile, the prevalence of counter-modern inclinations within these communities highlights the fans' constant devotion to the sport, demonstrating a profound loyalty. Collectively, these elements signify a shift from supporting specific teams to becoming keen fans of the broader sporting domain.